2018
DOI: 10.3221/igf-esis.47.34
|View full text |Cite
|
Sign up to set email alerts
|

A quick-assessment procedure to evaluate the degree of conservation of rockfall drapery meshes

Abstract: Drapery meshes are protection devices installed on a cliff for mitigating rockfall hazard. They can prevent the detachment of rock fragments and control the dynamics of the falling blocks. During their design working life, drapery meshes are subjected to ageing phenomena, corrosion and impact, which can invalidate the purposes of the protection devices. A novel procedure based on a multi-hierarchical assessment of the damages is proposed. The approach is tailored for two technologies well diffused in the Alps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For this purpose, based on the outcomes of past studies reported in the literature [20,21,23,98], and in-situ observations, different types of damages have been identified and classified into several groups related to: (i) surrounding context (i.e., connected with vegetation, variation in time of morphology); (ii) design, positioning and installation techniques; (iii) post-impact conditions (in the hypothesis that no maintenance is performed after the impact); (iv) aging, weathering, wearing and corrosion (in the hypothesis that no maintenance procedure is performed); and (v) incorrect maintenance procedures.…”
Section: Risk Management and Conservation Assessment Of Protection Dementioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, based on the outcomes of past studies reported in the literature [20,21,23,98], and in-situ observations, different types of damages have been identified and classified into several groups related to: (i) surrounding context (i.e., connected with vegetation, variation in time of morphology); (ii) design, positioning and installation techniques; (iii) post-impact conditions (in the hypothesis that no maintenance is performed after the impact); (iv) aging, weathering, wearing and corrosion (in the hypothesis that no maintenance procedure is performed); and (v) incorrect maintenance procedures.…”
Section: Risk Management and Conservation Assessment Of Protection Dementioning
confidence: 99%
“…Then, starting from the initial hypothesis that at the beginning of its working life the protection system has its maximum efficiency, i.e. assuming that it has been properly designed and positioned, a procedure able to evaluate the degree of degradation and to assess the state of conservation of both rockfall net fences and drapery mesh systems has been developed [98]. The method is based on a multi-criteria analysis, involving screening survey and providing a semi-quantitative value of the degree of conservation showing if the effectiveness is compromised, even though a complete assessment of the efficiency loss is far to be found.…”
Section: Risk Management and Conservation Assessment Of Protection Dementioning
confidence: 99%
“…In addition, due to their environmental exposure, net fences require a constant monitoring and maintenance, to guarantee their effectiveness and efficiency in time (Luciani et al 2018;Marchelli 2020;Jaccard et al 2020). A periodic inspection to assess the degree of conservation is thus suggested .…”
Section: Introductionmentioning
confidence: 99%
“…Infrastructure damage has been investigated (Bunce et al 1997;Budetta 2004;Mignelli et al 2012;Macciotta et al 2016;Mineo 2020). Passive protection structures such as embankments and fences are widely used to protect the infrastructure downhill of steep slopes (Ronco et al 2009;Peila and Ronco 2009;Marchelli et al 2019). Fences have been designed to intercept and withstand the impact of blocks, which are referred to as functional and structural designs, respectively (De Biagi et al 2020;Marchelli et al 2020).…”
Section: Introductionmentioning
confidence: 99%